Experimental and comparative toxicology - Rico, Andre G. (Advances in veterinary science and comparative medicine ;, 1987)
Experimental and Comparative Toxicology, Volume 31 aims to explore some of the potentially important and crucial areas in experimental toxicology. The book discusses tumor promoters and genotoxic chemicals in short-term testing for carcinogenicity, as well as the significance of preneoplastic liver lesions in experimental animals. The text also describes the factors known to be associated with increased risk of liver neoplasia as a human disease, and the extent to which it is known that the same factors have a similar effect in laboratory animals. Neurobehavioral toxicology; immunotoxicology.